Tinjauan Etika Profesi IT dalam Menghadapi Ancaman Cyber Crime di Indonesia - Evy Nurmiati; Muhammad Faiz Aqeel (Jurnal Sistem Informasi dan Ilmu Komputer, 2026)
This study aims to examine the role of information technology (IT) professional ethics as a preventive instrument in facing the escalation of cyber crime in Indonesia. Using the Systematic Literature Review (SLR) method with the PRISMA protocol, 17 selected scientific literature from the 2020-2026 period were analyzed comprehensively. The results of the study indicate that dominant operating modes such as ransomware on national infrastructure and mass data breaches in the banking and health sectors are rooted in the neglect of integrity and accountability principles. The discussion in this study confirms that the application of professional ethics based on the PAPA (Privacy, Accuracy, Property, Accessibility) framework is able to suppress the risk of internal threats and strengthen digital defense. The conclusion of the study shows that the synergy between the 2024 ITE Law regulations and the internalization of the professional code of ethics is the main key to data sovereignty in the digital era. The practical implications of this research recommend strengthening the ethics curriculum in IT higher education and ethical compliance audits in the public sector.